A Prospective Audit Investigating How the Anticholinergic Effect of Medications on Cognition Is Assessed and Reduced in Patients Admitted to an Older Adult Ward in a Psychiatric Hospital - Dinushi Marambe; Prami Rai (BJPsych Open)
Aims: Older adults often have multiple comorbidities associated with an increased risk of anticholinergic effects. Mental health medications increase this risk, contributing to cognitive decline, dementia, memory loss and confusion. Evidence suggests stopping these medications can reduce cognitive deterioration and progression of dementia. MediChec is an online tool that calculates an Anticholinergic Effect on Cognition (AEC) score. An AEC score above 2 and a total AEC score above 3 require a medication review for potential adjustment or deprescribing. This audit aims to determine whether the AEC scores were recorded at admission, during admission, and at discharge. Additionally, it assesses if further actions were taken to deprescribe unsuitable anticholinergics, resulting in a lower AEC score before discharge.